2021
DOI: 10.1021/acsmacrolett.1c00677
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Dependent Grain Coarsening of Block Copolymer Patterns under Controlled Solvent Evaporation

Abstract: Solvent evaporation annealing (SEA) is a straightforward, single-step casting and annealing method of block copolymers (BCP) processing yielding large-grained morphologies in a very short time. Here, we present a quantitative analysis of BCP graincoarsening in thin films under controlled evaporation of the solvent. Our study is aimed at understanding time and BCP concentration influence on the rate of the lateral growth of BCP grains. By systematically investigating the coarsening kinetics at various BCP conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Further investigations of the SEA mechanism revealed that a relatively narrow concentration window, just above the φ ODT (0.33 < φ < 0.40) facilitates rapid coarsening of BCP grains with the later drying stage inconsequential for the formation of large grains. 148 This result indicates the importance of the early stages of BCP ordering and underscores the utility of BCP processing strategies in which the ODT transition is crossed and grains are nucleated from a disordered state, an approach exploited in other direct casting methods and some field-assisted DSA methods. 149,150…”
Section: Review Of Solvent-assisted Self-assembly Of Bcp Filmsmentioning
confidence: 80%
See 4 more Smart Citations
“…Further investigations of the SEA mechanism revealed that a relatively narrow concentration window, just above the φ ODT (0.33 < φ < 0.40) facilitates rapid coarsening of BCP grains with the later drying stage inconsequential for the formation of large grains. 148 This result indicates the importance of the early stages of BCP ordering and underscores the utility of BCP processing strategies in which the ODT transition is crossed and grains are nucleated from a disordered state, an approach exploited in other direct casting methods and some field-assisted DSA methods. 149,150…”
Section: Review Of Solvent-assisted Self-assembly Of Bcp Filmsmentioning
confidence: 80%
“…Further investigations of the SEA mechanism revealed that a relatively narrow concentration window, just above the j ODT (0.33 o j o 0.40) facilitates rapid coarsening of BCP grains with the later drying stage inconsequential for the formation of large grains. 148 This result indicates 146 Copyright 2015 American Chemical Society, (c-e) adapted with permission from Macromolecules, 52, 5026. 147 Copyright 2019 American Chemical Society, (f-h) adapted with permission from Macromolecules, 53, 11178.…”
Section: Simultaneous Casting and Annealing Methodsmentioning
confidence: 97%
See 3 more Smart Citations